An experimental methodology to analyse the structural behaviour of FDM parts with variable process parameters. Issue 9 (14th July 2020) - Cerda-Avila, Steffany N.; Medellín-Castillo, Hugo Iván; Lim, Theodore
Abstract : Purpose: This paper aims to investigate the structural behaviour of polylactic acid (PLA) parts fabricated by fused deposition modelling (FDM) to support the development of analytical and numerical models to predict the structural performance of FDM components and categories of similar additive manufactured parts. Design/methodology/approach: A new methodology based on uniaxial tensile tests of filaments and FDM specimens, infill measurement and normalization of the results is proposed and implemented. A total of 396 specimens made of PLA were evaluated by using variable process parameters. Findings: The infill and the build orientation have a large influence on the elastic modulus and ultimate tensile stress, whereas the layer thickness and the infill pattern have a low influence on these properties. The elongation at break is not influenced by the process parameters except by the build orientation. Furthermore, the infill values measured on the test specimens differ from the nominal values provided by the system. Research limitations/implications: The analysis of the structural properties of FDM samples is limited to uniaxial loading conditions. Practical implications: The obtained results are valuable for the structural analysis and numerical simulation of FDM components and for potential studies using machine learning techniques to predict the structural response of FDM parts. Originality/value: A new experimental methodology that considers the measurement of the real infill percentage and the normalization of the results for inter-comparison with other studies is proposed. Moreover, a new set of experimental results of FDM-PLA parts is presented and extends the existing results in the literature.